Crystal structure of the triclinic form of (2tbpo·H +)2tetrachlorocuprate(II){[(PhCH2) 3PO]2H}2CuCl4: The presence of extremely short O-H-O interactions - Halvorson, Kristofer E.; Willett, Roger D.; Massabni, Antonio Carlos [UNESP] (Royal Society of Chemistry (RSC), 1990)
The structure of {[(PhCH2)3PO]2H} 2CuCl4 has been shown to contain four [(PhCH 2)3PO]2H+ cations with extremely short O-H-O distances of 2.295, 2.364, 2.394, and 2.404 Å, respectively.